A re-introduction of Pancasila from Neutrosophic Logic perspective: In search of the root cause of deep problems of modern societies - Victor Christianto; Robby Igusti Chandra; Florentin Smarandache (Cipanas Theological Seminary, 2021)
The present economic crises induced by covid pandemic have called our attention toreconsider where we are heading as a global community; because as we know withthe emergence of ubiquitous Internet, then the world has become a global village inreal sense.. Shall we lend ourselves to directive and -at times- insistence to move tonew economy called the industrial revolution 4.0? Or is there another way, even if itseems like a less traveled path for now? In this article, we also re-introduce Pancasilafrom Indonesian weltanschauung (fundamental tenets) to become one of these lesstravelled path available at our table. The essence of the Indonesian Five Principles(Pancasila) is to return to spirit of communal values, but in a peaceful way, not viarevolution. That is a path that in Indonesia, is called as “gotong royong” (or to put itin a more scientific term: cooperative collective dynamics).